The Majority of Patient-reported Outcome Measures in Pediatric Orthopaedic Research Are Used Without Validation. Issue 1 (January 2021) - Arguelles, Gabriel R.; Shin, Max; Lebrun, Drake G.; Kocher, Mininder S.; Baldwin, Keith D.; Patel, Neeraj M.
Abstract : Background: Given that patient-reported outcome measures (PROMs) are increasingly used to inform clinical decision-making, it is vital that they are validated, reliable, responsive, and appropriate for the population under study. The purpose of this systematic review was to assess the rate of PROM use in the pediatric orthopaedic literature, characterize whether each use was in the PROM-validated demographic, and analyze the association between bibliometric factors and the use of PROMs with incomplete validation. Methods: The Institute for Scientific Information (ISI) Web of Science database was queried for all clinical pediatric orthopaedic studies from 2014 to 2017. All PROMs were recorded for each study independently by 2 reviewers and cross-referenced with the published orthopaedic literature as of 2017 to determine if the PROM had been validated for the study population. PROMs that had not been validated, had been shown to be invalid, or had conflicting validity studies for use in the population of interest were designated as incompletely validated or used without complete validation. The following covariates were recorded for each study: subspecialty, inclusion of a statistician coauthor, sample size, journal, and the journal impact factor. χ 2 analysis was used to evaluate the association between categorical variables and the use of at least 1 incompletely validated PROM. Results: In total, 1000 articles were screened, yielding 653 studies that met our inclusion criteria. A total of 104/653 (16%) publications-reported PROMs. PROMs were used without complete validation 120/165 (73%) times, and 77/104 (74%) studies used at least 1 PROM without complete validation. The most frequent reasons for incomplete validation were (1) using PROMs that had been validated in adults, but not pediatrics (n=47; 28.5%), and (2) using PROMs that had been designated in the literature as invalid for pediatrics (n=27; 16.4%). The incomplete validation of at least 1 PROM was associated with smaller sample size ( P =0.01) and subspecialty ( P <0.01). Overall rates of PROM use and the proportion of PROMs used without complete validation were both found to be higher than those previously reported. Conclusion: The majority of pediatric orthopaedic studies reporting PROMs used at least 1 PROM without complete validation for their study population. Level of Evidence: Level IV—systematic review of level I, II, III, and IV studies. Abstract : Supplemental Digital Content is available in the text.